The Role of Public Space as a Provision for Marriage (Study of Instagram Accounts @birojodohrumaysho) - Handayani, Dwi Sri (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2022)
The digital revolution has caused many digital phenomena and issues related to society such as denomination and moral degradation and even the increase in divorce cases. Rising divorce cases are certainly urgent in the current discussion which is suspected by the lack of knowledge about marriage. As we know that marriage provisions are very important looking forward, there must be many domestic problems that arise. This research wants to see the role of the public space of family media and see the important point of this role as a provision for marriage for adolescents and young adults through this content This research is a type of field research (Field Research) which is carried out systematically by looking at the phenomena that exist in society and then connected with data on the instagram social media account of the birojodohrumaysho. However, because the data collection process refers to the application platform on the internet, this research can be called a study of phenomena on the internet, or in other terms nethography while the analysis is carried out using qualitative descriptive analysis by looking at field data and also the appropriate theory in this study, namely the theory of mass communication and media exposure. The results of this study describe 3 roles of the public space of family media, namely social transmission, 3 general points of role and purpose of relationships. In addition, openness in receiving information and applying it is an important thing as a result of media exposure that produces behavior.